Hydration and microstructural properties of cement paste containing nano and microsilica - Chow, P.; Barbhuiya, Salim (ISEC Press, 2014)
The influence of nano- and microsilica addition on ordinary Portland cement (OPC) pastes has been studied in terms of hydration and microstructural properties. Three different combinations of nano- and microsilica mixes were used. A constant water-binder ratio of 0.35 was maintained throughout the experiment. All samples were tested for initial and final setting time and compressive strengths were determined at the age of 3, 7, 28, and 90 days of hydration. The hydration products were examined by SDT and XRD analysis at various curing ages. The inclusion of nano- and microsilica reduced the initial and final setting time significantly, increased the compressive strength of hardened cement paste after 7 days of hydration, and reduced the amount of calcium hydroxide in the hardened paste compared to mixes without these nanoparticles.